RANCANG BANGUN MONITORING STATUS ACCESS POINT BERBASIS CRITICAL RATIO PADA PT. TELKOM INDONESIA DIVISI REGIONAL 5 - Hananto, Priyanggoro Dwi; Sukmaaji, Anjik; Soebijono, Tony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Telkom Indonesia as a state-owned telecommunications company, has a duty to to continue to develop the technology in Indonesia over the development period. One of the products that are currently in operation, namely public internet access has now spread all over Indonesia. With the number of Access Point (AP) which has spread especially on PT. Telkom Indonesia in Regional Division 5, is not easy to perform management and control at each AP. Thus PT. Indonesia Telkom Regional Division 5 requires the development of applications in managing and monitoring the AP. From this it has been proposed design of monitoring the status of the access point that can assist in managing and controlling the AP on PT. Indonesia Telkom Regional Division 5. In order to support in maintaining the stability of the status of AP, then the application of this method to manage the queue critical ratio improvement. From the test results indicate that the application status monitoring access point can bridge the relationship Manager, Supervisor and Field Technicians in managing and monitoring the AP. And the critical ratio meals will help manage queues improvement. Thus, application status monitoring access point can help Indonesia Telkom Regional Division 5 in maintaining the stability of the status of the AP.